(untitled) (Psicologia USP, 2013)
The objective of this study is to distinguish between two ways of thinking about femininity by psychoanalysis. The first, understood from the point of view of the libidinal economy of a man, and the second as a definite way of a subject to constitute itself as a sexed being. In order to develop this idea of femininity as a subject position we tried to establish connections among some of the key concepts that Freud and Lacan used to think about this theme, specially, in the case of Freud, with regard to the particular configuration of female libido between object libido and narcissistic libido and, in the case of Lacan, with regard to woman's relationship to the phallus to be mediated by a different form of relationship with the Other.